2012
DOI: 10.1080/13642987.2011.597747
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous peoples' rights and cultural identity in the inter-American context

Abstract: There is a wide set of rules and political documents that refer to the right to cultural identity, in particular with regard to Indigenous Peoples. However, the definition of a right to cultural identity as a human right has been criticised. The risk of tensions and conflicts based on religious or ethnicity grounds puts culture in a central place in the process of defining peoples' identity. This is a relevant issue in contemporary multicultural societies, not limited to indigenous rights. The concept of cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Among the recent publications (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) from the Journal of the Taiwan indigenous Studies Association, we found only two studies from business perspectives (Fan, 2015;Lin, 2017). Similarly, other studies are concerned with individual's rights and cultural identity (Odello, 2012), reconciliation (Short, 2003) and policies (Lithopoulos, 2007). In general, most of indigenous studies focus on individuals rather than organizations, even though their issues are interesting and attract attentions of academic researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Among the recent publications (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) from the Journal of the Taiwan indigenous Studies Association, we found only two studies from business perspectives (Fan, 2015;Lin, 2017). Similarly, other studies are concerned with individual's rights and cultural identity (Odello, 2012), reconciliation (Short, 2003) and policies (Lithopoulos, 2007). In general, most of indigenous studies focus on individuals rather than organizations, even though their issues are interesting and attract attentions of academic researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Now, it is known that the religious manifestations of these peoples have even been forbidden in many countries during the process of colonisation, even in Brazil (Costa and Carvalho 2019;Santos 2014) and the USA (Garroutte et al 2009). So, since the last century, they have become objects of protection for human rights movements, accompanied by legal justifications, recognition, and formalization in international law (Niezen 2017;Odello 2012). In 2007, the United Nations took a decisive step in this regard when it published its declaration on the rights of indigenous peoples, aiming at protecting the cultural and religious integrity of these peoples and guaranteeing them the right to express, practice, promote, and teach their spiritual and religious traditions and their customs and ceremonies (UN 2007).…”
Section: Spirituality Religiosity Religion and Indigenous Cosmologymentioning
confidence: 99%
“…As to the possession of land, Number VI of this section establishes limitations based on acquired rights of third parties and zones declared strategic. Some scholars argue that this provision restricts the recognition of ownership of land by indigenous people because, according to Article 27, the state owns their land, of which they are only beneficiaries (Gaona, 2013;Odello, 2012). In practice, they say, there is no real recognition of indigenous land rights, a situation that might be considered contrary to international law.…”
Section: Mexican Environmental Lawmentioning
confidence: 99%